1999
DOI: 10.1002/(sici)1521-4079(199904)34:4<449::aid-crat449>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Segregation in Vertical Bridgman Growth of GaInSb Alloys

Abstract: Cryst. Res. Technol. 34 1999 4 449-456 A set of experiments on the solidification of Ga 1-x In x Sb alloys with a large variation of the sample diameter (from 1mm to 10mm), of the growth rate (from 0.7 to 7 µm/s) and of the concentration (from x=0.01 to x= 0.1) is described. The associated radial and longitudinal segregation of the In have been analysed by SIMS or electron microprobe. Numerical simulation of the experiments, taking into account thermal, hydrodynamic and chemical behaviour has been carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…[7,14]. One experiment about the vertical Bridgman growth of 1% doped crystal has been also numerically analyzed in Ref.…”
Section: Comparison Of Numerical and Experimental Data In Bridgman Grmentioning
confidence: 99%
“…[7,14]. One experiment about the vertical Bridgman growth of 1% doped crystal has been also numerically analyzed in Ref.…”
Section: Comparison Of Numerical and Experimental Data In Bridgman Grmentioning
confidence: 99%
“…2D or 3D simulations would allow considering local faceting of the interface. electromagnetic levitation set-up has been developed in order to measure these thermo-physical properties [19]. It is found that the Si undercooling is a function of C concentration [20,21].…”
Section: Suggested Improvement For the Modelmentioning
confidence: 99%
“…Alloy segregation is a critical issue in the growth of bulk ternary III-V crystals [2]. These materials could provide lattice-matched substrates for epitaxial growth that eliminate the need for a graded bu®er layer and thus reduce the production costs and increase the life-time of semiconductor devices due to the lower density of the mis¯t dislocations.…”
Section: Phase Boundariesmentioning
confidence: 99%
“…The di±culty of growth of such ternary compounds as GaInAs and GaInSb stems from the large solidus-liquidus separation of the phase diagram and thus a small value of the In segregation coe±cient. The rejected solute accumulates at the interface and is transported by di®usion and convection, the latter having a major e®ect on the quality and the composition uniformity of the grown crystals [2,13]. Various defects such as striations or cellular structure in ternary In-containing crystals leading to poly-crystallinity when the solute concentration exceeds a critical value [47] are often observed.…”
Section: Phase Boundariesmentioning
confidence: 99%